Book Review: Communications And Media Law In Malaysia - Haliza A Shukor; Syahirah Abdul Shukor; Hendun Abd. Rahman Shah; Nik Salida Suhaila Nik Saleh; Resali Muda; Abidah Abdul Ghafar; Nazura Abdul Manap (Pusat Pengajian Teras, KUIS, 2024)
Non-Indexed Publication